The City of Pancevo’s Citizen Service Center, Serbia : Streamlining Service Delivery and Fostering Inclusion at the Municipal Level - Pfeil, Helene; Agarwal, Sanjay; Schott, Berenike Laura; Johns, Kimberly D. (World Bank, Washington, DC, 2017)
This case study provides an overview of the Pan evo Citizen Service Center (CSC), which, since its establishment in 2009, has delivered a variety of municipal services to citizens under one roof. It examines the measures established by the municipal team to guarantee equal access to services for all segments of the population and to improve the quality of service delivery, notably by migrating certain procedures online and providing citizens with rapid feedback mechanisms. While institutional coordination, funding, staff motivation, and capacity to meet demand remain challenges, the CSC has become a key focal point for the municipality, with the number of citizens visiting the center each year almost equaling the city’s inhabitants. Successes achieved through this local-level, one-stop-shop model include easier access, greater efficiency, faster delivery, improved communication, and better quality of information for citizens.